2020
DOI: 10.3390/cancers12020480
|View full text |Cite
|
Sign up to set email alerts
|

P-REX1-Independent, Calcium-Dependent RAC1 Hyperactivation in Prostate Cancer

Abstract: The GTPase Rac1 is a well-established master regulator of cell motility and invasiveness contributing to cancer metastasis. Dysregulation of the Rac1 signaling pathway, resulting in elevated motile and invasive potential, has been reported in multiple cancers. However, there are limited studies on the regulation of Rac1 in prostate cancer. Here, we demonstrate that aggressive androgen-independent prostate cancer cells display marked hyperactivation of Rac1. This hyperactivation is independent of P-Rex1 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Recent research showed that P-REX1 and Vav3 were served as the regulator of Rac1 in modulating the mobility of PCa. 9,10 In addition, RhoH, a regulator of Rac1, which depleted, is able to reduce lamellipodium extension by regulating the localization of Rac1. 11 However, Rho signaling network is complex, and the detail mechanism of Rac1 in mPCa remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research showed that P-REX1 and Vav3 were served as the regulator of Rac1 in modulating the mobility of PCa. 9,10 In addition, RhoH, a regulator of Rac1, which depleted, is able to reduce lamellipodium extension by regulating the localization of Rac1. 11 However, Rho signaling network is complex, and the detail mechanism of Rac1 in mPCa remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of the Rac1 signaling pathway, resulting in elevated motile and invasive potential, has been reported in PCa. Recent research showed that P‐REX1 and Vav3 were served as the regulator of Rac1 in modulating the mobility of PCa 9,10 . In addition, RhoH, a regulator of Rac1, which depleted, is able to reduce lamellipodium extension by regulating the localization of Rac1 11 .…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, we first used prostate cancer cell lines with different levels of basal Rac1-GTP. We have previously shown that androgen-independent aggressive cell lines DU145, PC3, and PC3-ML have high levels of basal active Rac1 when compared with a normal prostate epithelial cell line (RWPE1), prostate hyperplasic cell line (BPH-1), and less aggressive prostate cancer cell lines (LNCaP and LNCaP variants), which all have low levels of Rac1-GTP (56) (Fig. 6A).…”
Section: Examples Of Misleading Results With the Anti-rac1-gtp Antibomentioning
confidence: 91%
“…The extensive interest of our laboratory in the role of Rac1 signaling in tumorigenesis and metastasis (3,56,57) prompted us to use the anti-Rac1-GTP antibody in a number of cancer cell models. In the course of these studies, we stumbled upon a number of inconsistencies that persuaded us to pursue a deeper characterization of this antibody.…”
mentioning
confidence: 99%
“…In this study, we identified that P-Rex1 was overexpressed in liver tumor tissues (Figures 1 and 4 ), which was consistent with previous reports in other cancers. Baker et al[ 33 ] reported hyperactivation of P-Rex1 in prostate cancer[ 33 ]. P-Rex1 amplification is also involved in the progression of melanoma via the PAK1/P38 pathways[ 34 ].…”
Section: Discussionmentioning
confidence: 99%